Maize-soybean relay strip intercropping reshapes the rhizosphere bacterial community and recruits beneficial bacteria to suppress Fusarium root rot of soybean - Chang, Xiaoli; Wei, Dengqin; Zeng, Yuhan; Zhao, Xinyu; Hu, Yu; Wu, Xiaoling; Song, Chun; Gong, Guoshu; Chen, Huabao; Yang, Chunping; Zhang, Min; Liu, Taiguo; et al. (Frontiers in Microbiology, 2022)
Rhizosphere microbes play vital role in plant health and defense against soil-borne diseases. Previous studies showed that maize-soybean relay strip intercropping altered the diversity and composition of pathogenic Fusarium species and biocontrol fungal communities in soybean rhizosphere, and significantly suppressed soybean root rot. However, whether rhizosphere bacterial community participates in the regulation of this intercropping on soybean root rot is not clear. In this study, the rhizosphere soil of soybean healthy plants were collected in the continuous cropping of maize-soybean relay strip intercropping and soybean monoculture in the fields, and the integrated methods of microbial profiling, dual culture assays in vitro and pot experiments were employed to systematically investigate the diversity, composition and function of rhizosphere bacteria related to soybean root rot in two cropping patterns. We found that intercropping reshaped rhizosphere bacterial community and increased microbial community diversity, and meanwhile it also recruited much richer and more diverse species of Pseudomonas sp., Bacillus sp., Streptomyces sp., and Microbacterium sp. in soybean rhizosphere when compared with monoculture. From the intercropping, nine species of rhizosphere bacteria displayed good antagonism against the pathogen Fusarium oxysporum B3S1 of soybean root rot, and among them IRHB3 (Pseudomonas chlororaphis), IRHB6 (Streptomyces) and IRHB9 (Bacillus) were the dominant bacteria and extraordinarily rich. In contrast, MRHB108 (Streptomyces virginiae) and MRHB205 (Bacillus subtilis) were only antagonistic bacteria from monoculture were relatively poor in abundance. Interestingly, introducing IRHB3 into the cultured substrates not only significantly promoted the growth and development of soybean roots but also improved the survival rate of seedlings which suffered from F. oxysporum infection. Thus, this study proves that maize-soybean relay strip intercropping could help the host resist soil-borne Fusarium root rot by reshaping the rhizosphere bacterial community and driving more beneficial microorganisms to accumulate in soybean rhizosphere.